Public perceptions on the importance of ecosystem services from vulnerable forest: a case study of Ampang Forest Reserve, Selangor, Malaysia - Gai, Mei Yin; Hassan, Muhammad Luqman; Anak Empidi, Arlixcya Vinnisa; Juraimi, Umi Farishaanum; Mohd Noorazman, Nurashikin; Emang, Diana (Department of Forest Management, 2024)
Forest reserve degazettement affects the sustainability of forests by altering their ecological functions, hence threatening human livelihoods. This study examines a recently degazetted forest, using a survey of 120 local respondents living near the Ampang Forest Reserve (AFR) in Selangor, Malaysia. A simple random sampling technique was implemented to reduce sampling bias, and descriptive and correlation statistics were used in the analysis. The study aimed a) to examine the public perceived importance of forest ecosystem services from the AFR, b) to determine public awareness of a range of environmental threat levels towards the AFR's ecosystem services, and c) to assess public agreement on conservation measures that could increase protection and ensure the sustainability of ecosystem services from the remaining area of the AFR. The results revealed that all ecosystem services were perceived as important, and the public was mostly aware of environmental threats. At the same time, conservation measures should be implemented to protect and ensure the sustainability of ecosystem services from the AFR. This study provides insights into public perceptions of the importance of forest ecosystem services derived from vulnerable forest reserves. This indicates the relevance and need for better protection in high-risk forest areas, as local livelihood depends on its significant ecological roles.